Light‐Patterned Crystallographic Direction of a Self‐Organized 3D Soft Photonic Crystal. Issue 42 (28th August 2017) - Zheng, Zhi‐Gang; Yuan, Cong‐Long; Hu, Wei; Bisoyi, Hari Krishna; Tang, Ming‐Jie; Liu, Zhen; Sun, Pei‐Zhi; Yang, Wei‐Qiang; Wang, Xiao‐Qian; Shen, Dong; Li, Yannian; Ye, Fangfu; et al.
Abstract: Uniform and patterned orientation of a crystallographic direction of ordered materials is of fundamental significance and of great interest for electronic and photonic applications. However, such orientation control is generally complicated and challenging with regard to inorganic and organic crystalline materials due to the occurrence of uncontrollable dislocations or defects. Achieving uniform lattice orientation in frustrated liquid‐crystalline phases, like cubic blue phases, is a formidable task. Taming and tailoring the ordering of such soft, cubic lattices along predetermined or desired directions, and even imparting a prescribed pattern on lattice orientation, are more challenging, due to the entropy‐domination attribute of soft matter. Herein, we disclose a facile way to realize designed micropatterning of a crystallographic direction of a soft, cubic liquid‐crystal superstructure, exhibiting an alternate uniform and random orientation of the lattice crystallographic direction enabled by a photoalignment technique. Because of the rewritable trait of the photoalignment film, the pattern can be erased and rewritten on‐demand by light. Such an oriented soft lattice sensitively responds to various external stimuli such as temperature, electric field, and light irradiation. Furthermore, advanced reflective photonic applications are achieved based on the patterned crystallographic orientation of the cubic blue phase, soft lattice. Abstract : A facile way to realize designed micropatterning of a crystallographic direction of a soft, cubic liquid‐crystal superstructure is disclosed, exhibiting an alternate uniform and random orientation of the lattice crystallographic direction, enabled by a photoalignment technique, which has not been accomplished before.